The Determinants of Stock Market Development in Emerging Economies : Is South Africa Different? - Yartey, Charles Amo. (Washington, D.C. : International Monetary Fund, 2008)
This paper examines the institutional and macroeconomic determinants of stock market development using a panel data of 42 emerging economies for the period 1990 to 2004. The paper finds that macroeconomic factors such as income level, gross domestic investment, banking sector development, private capital flows, and stock market liquidity are important determinants of stock market development in emerging market countries. The results also show that political risk, law and order, and bureaucratic quality are important determinants of stock market development because they enhance the viability of external finance. This result suggests that the resolution of political risk can be an important factor in the development of emerging stock markets. The analysis also shows the factors identified above as determining stock market development in emerging economies can also explain the development of the stock market in South Africa.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet